Preserving Artistic Heritage: Legal Protection for Intellectual Property Rights in the Music Industry : Penelitian - Zakiya Putri Az-Zahra; Rina Arum Prastyanti (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to examine the legal framework governing copyright protection for creative economy actors and analyze the legal culture among these actors from the perspective of copyright enforcement in Indonesia. This study uses an empirical juridical method, applying a legal research approach that is in accordance with the philosophical nature of legal science. In practice, the Copyright Law remains unclear and insufficiently firm in regulating the protection of moral rights, potentially resulting in the omission of copyright recognition for works reproduced or used in public, as well as the absence of explicit recognition of copyright claims. Nevertheless, the law successfully addresses two main objectives in the development of the creative economy: providing legal protection and economic incentives. From a cultural perspective, creative economy actors find it relatively easy to register their works for legal protection. However, they also face a number of challenges, such as a lack of understanding of copyright principles, the rapid development of technology and digital media, rampant piracy, and the high cost of taking legal action to defend intellectual property rights.